Liverwort oil bodies: diversity, biochemistry, and molecular cell biology of the earliest secretory structure of land plants. (8th April 2022) - Romani, Facundo; Flores, Jorge R; Tolopka, Juan Ignacio; Suárez, Guillermo; He, Xiaolan; Moreno, Javier E
Abstract : This review outlines the evolutionary history of oil bodies in liverworts and their relationship with the chemical diversity of the lineage. Abstract: Liverworts are known for their large chemical diversity. Much of this diversity is synthesized and enclosed within oil bodies (OBs), a synapomorphy of the lineage. OBs contain the enzymes to biosynthesize and store large quantities of sesquiterpenoids and other compounds while limiting their cytotoxicity. Recent important biochemical and molecular discoveries related to OB formation, diversity, and biochemistry allow comparison with other secretory structures of land plants from an evo-devo perspective. This review addresses and discusses the most recent advances in OB origin, development, and function towards understanding the importance of these organelles in liverwort physiology and adaptation to changing environments. Our mapping of OB types and chemical compounds to the current liverwort phylogeny suggests that OBs were present in the most recent common ancestor of liverworts, supporting that OBs evolved as the first secretory structures in land plants. Yet, we require better sampling to define the macroevolutionary pattern governing the ancestral type of OB. We conclude that current efforts to find molecular mechanisms responsible for the morphological and chemical diversity of secretory structures will help understand the evolution of each major group of land plants, and open new avenues in biochemical research on bioactive compounds in bryophytes and vascular plants.